Hands and feet radiologic involvements in systemic sclerosis - Fatemeh Badiee; Alireza Fatemi; Reza Zahedpasha; Mohammad Hadi Gharib; Mohammadhassan Jokar; Somayeh Livani; Mehrdad Aghaie; Nafiseh Abdolahi (BMC Rheumatology, 2023)
Abstract Aim Systemic sclerosis (SSc) is a rare autoimmune disorder characterized by vascular and fibrosing involvement of the skin and internal organs. In this study, we determined the prevalence and characteristics of radiological hands and feet involvements in Iranian SSc patients to identify the associations between clinical features and radiologic findings. Methods 43 SSc patients (41 women and 2 men), with a median age of 44.8 years (ranges 26–70 years) and a mean disease duration of 11.8 years (ranges 2–28 years) were studied in this cross-sectional study. Results 42 patients had radiological changes both in their hands and feet. Only one patient had alteration just in hand. The most frequent changes that we found in hand were Juxta-articular Osteoporosis (93%), Acro-osteolysis (58.2%), and Joint Space Narrowing (55.8%). The prevalence of joint space narrowing or acro-osteolysis was higher in subjects with active skin involvement [modified Rodnan skin score (mRSS) > 14] [16/21 vs. 4/16 for patients with inactive skin involvement (mRSS < 14); p = 0.002]. The most frequent changes that we found in the foot were Juxta-articular Osteoporosis (93%), Acro-osteolysis (46.5%), Joint Space Narrowing (58.1%), and subluxation (44.2%). The presence of anti-ccp antibody was detected in 4 (9.3%), while positive rheumatoid factor was found in 13 (30.2%) of SSc patients. Conclusion This study corroborates that arthropathy is common in SSc patients. The introduction of the specific radiological involvements of SSc needs to be confirmed by further studies, in order to define the appropriate prognosis and treatment of patients.